Investigating diversity of botanic resource at Linh Thong commune, Dinh Hoa district, Thai Nguyen province - Hung, Nguyen Anh; Tan, Le Dong; Ngoc Mai, Ma Thi (Academia Journal of Biology, 2013)
Linh Thong is a commune located at the North of Dinh Hoa district, Thai Nguyen province. Local people of the commune are mainly rely on agriculture and forestry products. The areas of forest are mainly on rocky mountains. Our survey showed that there are 121 species belonging to 110 sub-branches, 65 families of 4 branches of high-developed vessel botany in Dinh Hoa forest. Of the total plant living forms, there are mainly trees, brushes, soft-stems and creepers. Among those, the trees and soft-stems are highest. Based on the use values, Plant species can be categorized to the following groups: giving wood, medicine and food (species giving fruit and wild vegetables), decoration, oil essence. At the present, the plant resource is over-exploited by inhabitants and it may result in the risk of exhausting, thus measurements of conservation of this resource are needed immediately.